Multistage math model of support decision decisions in the stochastic demand - Нефьодов, Леонід Іванович; Маркозов, Дмитро Олександрович (Eastern-European Journal of Enterprise Technologies, 2010)
The paper developed a multistage mathematical model management multinomenclature stock under stochastic demand with many constraints. The result application of the presented model is to obtain rapid and optimal size plan for resupply, thus enhancing the efficiency decision management solutions.